2012
DOI: 10.1177/0018720812441796
|View full text |Cite
|
Sign up to set email alerts
|

Simulator Training With a Forward Collision Warning System

Abstract: Objective: The study addressed the role of familiarization on a driving simulator with a forward collision warning (FCW) and investigated its impact on driver behavior. Background: Drivers need a good understanding of how an FCW system functions to trust it and use it properly. Theoretical and empirical data suggest that exploring the capacities and limitations of the FCW during the learning period improves operating knowledge and leads to increased driver trust in the system and better driver-system interac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
8
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 57 publications
(10 citation statements)
references
References 31 publications
2
8
0
Order By: Relevance
“…Research has shown that as expertise increases, there may be a direct increase in trust (Merritt, Lee, Unnerstall, & Huber, 2015; Rajaonah, Anceaux, & Vienne, 2006; Schaefer, Chen, Szalma, & Hancock, 2016). Similar results for familiarity affecting trust have been found with collision warning systems (Koustanaï, Cavallo, Delhomme, & Mas, 2012) and takeover performance (Hergeth, Lorenz, & Krems, 2017). Additional work has suggested that trust calibration can be enhanced through presentation of trust cues (de Visser, Cohen, Freedy, & Parasuraman, 2014), decision aids (McGuirl & Sarter, 2006), greater transparency (Yang, Unhelkar, Li, & Shah, 2017), causal attributions of automation failures (Pop, Shrewsbury, & Durso, 2015), and system uncertainty (Helldin, Falkman, Riveiro, & Davidsson, 2013).…”
Section: Introductionsupporting
confidence: 76%
“…Research has shown that as expertise increases, there may be a direct increase in trust (Merritt, Lee, Unnerstall, & Huber, 2015; Rajaonah, Anceaux, & Vienne, 2006; Schaefer, Chen, Szalma, & Hancock, 2016). Similar results for familiarity affecting trust have been found with collision warning systems (Koustanaï, Cavallo, Delhomme, & Mas, 2012) and takeover performance (Hergeth, Lorenz, & Krems, 2017). Additional work has suggested that trust calibration can be enhanced through presentation of trust cues (de Visser, Cohen, Freedy, & Parasuraman, 2014), decision aids (McGuirl & Sarter, 2006), greater transparency (Yang, Unhelkar, Li, & Shah, 2017), causal attributions of automation failures (Pop, Shrewsbury, & Durso, 2015), and system uncertainty (Helldin, Falkman, Riveiro, & Davidsson, 2013).…”
Section: Introductionsupporting
confidence: 76%
“…They found that the more drivers were exposed to FCW, the faster they can react to the signal. This is also confirmed by Koustanaï et al (2012) where the FCW was more effective with familiarized drivers compared to unfamiliarized. Variations of driver reaction considering above parameters are considered in this paper by including a large range of driver reaction time (from 0.6 to 1.2s) but are not varied depending on driver's characteristics in our samples.…”
Section: Discussionsupporting
confidence: 59%
“…It appeared that the more exposed were drivers to FCW, the faster they reacted to the signal. Koustanaï et al (2012) determined FCW effects on drivers. They showed that drivers' interaction with FCW system were more effective when drivers were familiarised with the system compared to unfamiliarised drivers.…”
Section: Introductionmentioning
confidence: 99%
“…Alarms for collision warning systems should also be reliable (Bliss & Acton, 2003). Koustanai, Cavallo, Dalhomme, & Mas (2012) suggest that individuals familiar with how the collision warning system functions tend to trust the system more than those who were unfamiliar with the system. Research into perceptual aids suggests that there was no significant difference in trust for varying levels of automation in a fault management system (Lorenz, De Nocera, Rottger, & Parasuraman, 2002).…”
Section: The Environmentmentioning
confidence: 99%